Models and their IT Application for Search Planning - Andrzej NAJGEBAUER; Jarosław RULKA; Wojciech KULAS (Communications of International Proceedings, 2020)
The article is devoted to the modelling and planning method of searching the area in order to find the missing person. In the introduction we present scenarios and concepts in the field of search theory, referring to recognized sources of literature in this field. In addition, we present methods for evaluating the effectiveness of a site search, based on the theory and own studies introduced earlier. The most important part of the work is the search planning method taking into account field conditions, resources and qualifications of the searchers. Both the optimization model and the heuristic method of solving the formulated sentence are original. The application developed on this basis has been integrated with the system for collecting and processing information about missing persons in the framework of a geo-location server called CEZAR. The method has been tested for a number of cases. Selected cases are presented here.
Keywords: Searching missing person; optimization model of search planning; IT search planning application.